Molecular and Pharmacokinetic Aspects of the Acetylcholinesterase-Inhibitory Potential of the Oleanane-Type Triterpenes and Their Glycosides - Katarzyna Stępnik; Wirginia Kukula-Koch; Wojciech Płaziński (Biomolecules, 2023)
The acetylcholinesterase-inhibitory potential of the oleanane-type triterpenes and their glycosides from thebark of Terminalia arjuna (Combreatceae), i.e.,arjunic acid, arjunolic acid, arjungenin, arjunglucoside I, sericic acid and arjunetin, is presented. The studies are based on in silico pharmacokinetic and biomimetic studies, acetylcholinesterase (AChE)-inhibitory activity tests and molecular-docking research. Based on the calculated pharmacokinetic parameters, arjunetin and arjunglucoside I are indicated as able to cross the blood–brain barrier. The compounds of interest exhibit a marked acetylcholinesterase inhibitory potential, which was tested in the TLC bioautography test. The longest time to reach brain equilibrium is observed for both the arjunic and arjunolic acids and the shortest one for arjunetin. All of the compounds exhibit a high and relatively similar magnitude of binding energies, varying from ca. −15 to −13 kcal/mol. The superposition of the most favorable positions of all ligands interacting with AChE is analyzed. The correlation between the experimentally determined IC50 values and the steric parameters of the molecules is investigated. The inhibition of the enzyme by the analyzed compounds shows their potential to be used as cognition-enhancing agents. For the most potent compound (arjunglucoside I; ARG), the kinetics of AChE inhibition were tested. The Michaelis–Menten constant (Km) for the hydrolysis of the acetylthiocholine iodide substrate was calculated to be 0.011 mM.